Feeding regimen modulates zebrafish behavior - Dametto, Fernanda S.; Fior, Debora; Idalencio, Renan; Rosa, Joao Gabriel S.; Fagundes, Michele; Marqueze, Alessandra; Barreto, Rodrigo E. [UNESP]; Piato, Angelo; Barcellos, Leonardo J. G. (Peerj Inc, 2018)
Here we show that the feeding regimen modulates zebrafish (panic) rerio) behavior. With regard to the time elapsed between feeding and behavioral evaluation, fish fed 3 h before behavioral evaluation in the novel tank test (NTT) showed decreased activity and a trend toward an an)dolytic reaction (increased use of the upper section of the aquarium) in comparison to fish fed 0.5, 6, 12, 24 or 48 h before. testing, although fferences were not statistically,significant for all comparisons.Activity and use of the upper section of the aquarium did not differ significantly among the other treatments. Regarding feeding frequency, fish fed once a day showed higher anxiety-like behavior (decreased use of the upper section of the aquarium) in comparison to fish fed twice a day but feeding four or six times Per day or only every second day did not result in differences from feeding twice a day. Feeding frequency had no effect on activity level. Metabolically, fish fed once a day presented decreased levels of glucose and glycogen and increased lactate when compared to the regular feeding (fish fed twice a day),suggesting that feeding regimen may modulate carbohydrate metabolism. Mechanistically we suggest that the metabolic changes caused by the feeding regimen may induce behavioral changes. Our results suggest that the high variability of the results among different laboratories might be related to different feeding protocols. Therefore, if issues pertaining to the feeding regimen are not considered during experiments with zebrafish, erroneous interpretations of atasets may occur.
Keywords: Anxiety; Novel tank test; Danio rerio; Energetic metabolism; Feeding frequency